Efektivitas Pembelajaran Jarak Jauh (PJJ) Pada Masa Pandemi Covid-19 di FKIP Universitas Mathla’ul Anwar Banten - Purlilaiceu Purlilaiceu (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
This research was conducted to obtain data on the effectiveness of distance or online learning during the Covid-19 pandemic at the Mathla ul Anwar Banten Teaching and Education Faculty. The method used in this research is descriptive quantitative. Based on the method that has been determined by the author, the method of data collection is through online questionnaires using google form. Questionnaires or questionnaires distributed to students ask about the effectiveness of distance learning during the Covid-19 pandemic. The respondents in this study were 60 respondents who were chosen randomly or randomly. Presentation of data in this study includes descriptions and data analysis, as well as interpretation of research results. Based on the results of the questionnaire, it can be obtained data that some students do not find it difficult in implementing the distance learning process but students experience physical problems or lack of concentration, causing boredom during distance learning that occurred during the Covid-19 pandemic.